Dynamic feeder dyke systems in basaltic volcanoes: the exceptional example of the 1809 Etna eruption (Italy) - Geshi, Nobuo; Neri, Marco (Frontiers in Earth Science, 2014)
In this paper, we describe the 1809 eruption of Mt. Etna, Italy, which represents one historical and rare case in which it is possible to closely observe the internal structure of the feeder system. This is possible thanks to the presence of two large pit craters located in the middle of the eruptive fracture field that allow studying a section of the shallow feeder system. Along the walls of one of these craters, we analysed well-exposed cross sections of the uppermost 15–20 m of the feeder system and related volcanic products. Here, we describe the structure, morphology and lithology of this portion of the 1809 feeder system, including the host rock which conditioned the propagation of the dyke, and compare the results with other recent eruptions. Finally, we propose a dynamic model of the magma behaviour inside a laterally–propagating feeder dyke, demonstrating how this dynamic triggered important changes in the eruptive style (from effusive/Strombolian to phreatomagmatic) during the same eruption. This is therefore an exceptional case to understand how basaltic magmas move during the propagation of an eruptive fissure. Our results are also useful for hazard assessment related to the development of flank eruptions, potentially the most hazardous type of eruption from basaltic volcanoes in densely urbanized areas like those at Mt. Etna.